Sosialisasi dan Edukasi Masyarakat dalam Pencegahan Penanggulangan Bencana Kebakaran di Permukiman Padat Perkotaan - Ari Sulistyanto; Pagi Muhamad; Tabrani Sjahrizal; Abdul Haris; Dwinarko Dwinarko (Yayasan Literasi Sains Indonesia, 2026)
Fire is one of the non-natural disasters with a high level of risk, particularly in densely populated residential areas in urban regions such as Cakung Timur Subdistrict, East Jakarta. The low level of community knowledge, skills, and preparedness in dealing with fire hazards constitutes a major problem that potentially increases the extent of losses. This community service activity aims to enhance community capacity through socialization and education on community-based fire prevention and mitigation. The methods employed include observation, material preparation, implementation of socialization and educational activities, fire response simulations, and evaluation. The results indicate a significant improvement in community knowledge, skills, and awareness regarding fire risks. This is evidenced by the increase in pre-test results from 30% to 90.5% in the post-test. Participants were able to identify the causes of fire, understand preventive measures, and demonstrate the use of fire extinguishers and evacuation procedures. In addition, the development of an understanding of emergency communication systems has improved coordination among community members in dealing with emergency situations. Therefore, an approach that integrates socialization, education, and simulation has proven effective in enhancing community-based preparedness. This activity is expected to serve as a model for fire risk mitigation that can be replicated in other areas with similar characteristics.